36-(6-х)^2 =х(2,5-х) (2-х)^2 -х(х+1,5)=4 подробно,

teta89p016as teta89p016as    3   08.10.2019 16:20    0

Ответы
olyavlas23 olyavlas23  10.10.2020 04:41

36-(6-х)² =х(2,5-х)

36-36+12х-х²=2,5х-х²

9,5х=0     х=0

(2-х)² -х(х+1,5)=4

4-4х+х²-х²-1,5х=4

-5,5х=0      х=0

ПОКАЗАТЬ ОТВЕТЫ
дашуля298 дашуля298  10.10.2020 04:41

1. 36-(36-12х+х^2)=2,5х-х^2

36-36+12х-х^2-2,5х+х^2=0

12х-2,5х=0

9,5х=0

Х=0

2.

(2-х)^-х(Х+1,5) =4

4-4х+х^ - х^ -1,5х = 4

4-5,5х=4

-5,5х = 4-4

-5,5х =о

Х=0

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика